Absorption of Cu(II) in layered diaminoalkyl- and monoaminoalkyl-polysilsesquioxane. (6th December 2017) - Takagi, Teppei; Kawamura, Izuru; Oumi, Yasunori; Miwa, Yohei; Yoshitake, Hideaki
Abstract: Lamellar polysilsesquioxane containing two kinds of aminoalkyl groups were synthesized using alkanoic acids. Our intension with this synthesis was to increase the exposure to the absorbate of the absorption sites in the polymer solid without sacrificing its high density of sites. That is, this method is designed to weaken the interactions around the amine sites that inhibit diffusion of the aqueous cation pollutants. The mixing ratio, x : y, of 3-aminopropyltrimethoxysilane (AP silane) and N-(aminoethyl)-3-aminopropyltrimethoxysilane (AeAP silane) in the liquid precursor agrees well with that of the AP and AeAP groups in the solid, [(C13 H27 COOH) x (C12 H23 CH(COOH)CH2 COOH) y (NH2 C3 H6 ) x (NH2 C2 H4 NHC3 H6 ) y Si10 O15 ]n or [(MAS) x (C12SA) y (AP) x (AeAP) y Si10 O1.5 ]n ( x + y = 10). A good lamellar structure was obtained with x : y ratio higher than 2: 8. FT-IR spectroscopy reveals that increasing the x : y ratio enhances the bands due to hydrogen-bonded –COOH and dissociated –COO -, suggesting an increase in water molecule insertion around the carboxyl and amine groups with x : y . In 13 C CP-MAS NMR, unresolved peaks due to carboxylate carbons disappear at x : y = 4: 6 and 2: 8, suggesting that carboxylate is isolated at these mixing ratios probably due to hydration. In addition, continuous growth of the peak due to ionized carboxylate is observed. The amount of absorbed aqueous Cu(II) is particularly large when x : y = 4: 6, which is revealed by analysis with the Langmuir equation. In contrast, the ESR spectrum of Cu(II) is independent on the x : y ratio, suggesting the accessibility of the absorption sites is simply improved when x : y = 4: 6. It is likely that this mixing ratio provides a particularly effective structure for exposing the absorption sites of aqueous Cu(II). Graphical abstract: Highlights: Lamellar polysilsesquioxane containing mono- and diaminoalkyl groups were synthesized using carboxylate template. We increase the exposure to aqueous pollutant absorbate of the absorption sites in the self-assembled solid. The water occluded in the solid was estimated by the ionization of carboxylate. The amount of absorbed aqueous Cu(II) is particularly large when monoaminoalkyl: diaminoalkyl = 4: 6. The amount of absorption of Cu(II) and the ionization of template carboxylate are well correlated.